Normative foundations - Zhang, KA (2022)
This dissertation presents a theory of normativity. The central claim to be advanced is that human beings are constitutively committed to certain objective moral and other normative requirements. Furthermore, setting itself against the proposition that there are brute and mind-independent normative facts, the dissertation also advances positive theses about how normativity arises from the mind, as well as why a mind-given theory of normativity need not be nihilistic. After advancing this positive vision of normativity, the dissertation turns to examine prominent arguments for moral objectivity from Christine Korsgaard, Michael Smith, Julia Markovits, and Sharon Street.